Changing patterns of first medical contact management profile of corneal ulcers in a developing country: a hospital-based study - Kumar, Santosh; Sharma, Vijay K. (International Journal of Research in Medical Sciences, 2020)
Background: Infectious keratitis is a major cause of corneal blindness throughout the world. There are guidelines and protocols for management of infectious keratitis, but these are rarely practiced by the treating physician. The aim of this study is to find the first medical contact management profile in a tertiary care Centre in north India and compare it to the previous studies to see the changing patterns of first contact management in our country. Methods: The data for the study was collected by retrospective data review of 100 consecutive patients with infectious keratitis. Various parameters were studied and statistical correlation established, where it was felt necessary. The parameters were age and sex distribution, first medical contact, initial treatment prescribed, time interval for first medical contact, inciting factors for corneal ulcer, bacterial and fungal culture spectrum, visual recovery after medical and surgical treatment. Results: Data review of 100 consecutive patients with infectious keratitis was done. More than 70% of patients were above 40 years of age. In 54% of patients, no inciting agent could be identified. The first medical contact for majority of patients was ophthalmologists in independent practice (48%). Time interval for first contact to any health professional varied from one day to 75 days with mean 4.63 days. Moxifloxacin hydrochloride eye drops was the most commonly used drug. Staphylococcus epidermidis was the commonest isolate grown in the culture (38.9%). Conclusions: Early diagnosis and appropriate management of infectious keratitis is important and role of first medical contact of patient is most crucial in final outcome.